2016
DOI: 10.1080/00016489.2016.1230681
|View full text |Cite
|
Sign up to set email alerts
|

Sialendoscopy under local anaesthesia

Abstract: The level of discomfort and pain experienced during the operation was assessed as 'mild' or 'none' by 85% and 89% of the patients, respectively. The level of pain experienced after the operation was 'major' in 4% of patients and 'mild' or 'none' in the majority (87%) of patients. The patients' estimations showed no significant difference between the diagnostic and interventional procedures, although it seems that patients who underwent stone removal by transoral incision experienced the operation as a bit more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…There is an absence of literature reporting pain levels and pain management following sialendoscopy. Jokela et al reported pain prior to discharge among 89 patients who received sialendoscopy: 87% reported mild‐to‐no pain, and 67% of their patients did not require postoperative pain medication . Their findings suggest that sialendoscopy rarely necessitates opioids for managing pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an absence of literature reporting pain levels and pain management following sialendoscopy. Jokela et al reported pain prior to discharge among 89 patients who received sialendoscopy: 87% reported mild‐to‐no pain, and 67% of their patients did not require postoperative pain medication . Their findings suggest that sialendoscopy rarely necessitates opioids for managing pain.…”
Section: Discussionmentioning
confidence: 99%
“…Jokela et al reported pain prior to discharge among 89 patients who received sialendoscopy: 87% reported mild-to-no pain, and 67% of their patients did not require postoperative pain medication. 17 Their findings suggest that sialendoscopy rarely necessitates opioids for managing pain. Cramer et al classified sialendoscopy and salivary gland surgery as intermediate-pain procedures for which they recommended a multimodal postoperative pain regimen.…”
Section: Sialendoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Konstantinidis et al [15] and Papadopoulou-Alataki et al [1] reported favorable outcome of sialendoscopy under local anesthesia in children and adolescents >8 years of age [1, 15]. Jokela et al [23] published very encouraging results on the tolerability of sialendoscopy under local anesthesia in adult patients with JRP [23].…”
Section: Diagnosismentioning
confidence: 99%
“…The development of modern sialendoscopy has allowed improved visual access into the salivary duct system to diagnose and treat obstructive causes. Sialendoscopy can be performed under local anesthesia with minimal morbidity [9,10]. Good results have been achieved in the treatment of sialolithiasis and ductal stenosis or strictures [11].…”
Section: Introductionmentioning
confidence: 99%